The Taxation of Interest in Europe: A Minimum Withholding Tax? - Harry Huizinga; Søren Bo Nielsen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
This paper provides an analysis of the proposal for introducing a minimum withholding tax on interest in the EU. We present a model with three countries: a typical EU country, an 'inside' tax haven, and an 'outside' tax haven. In the initial non-cooperative solution, the former two countries impose withholding taxes on interest. We investigate what happens to welfare in these countries, if the 'inside' tax haven is forced to raise its withholding tax. From the model we proceed to a broader evaluation of the minimum withholding tax proposal.
Keywords: 330